Motivating Factors for Teachers: Case Study Analysis - Vanagas, Ramūnas; Čižikienė, Janina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article analyses the problem of teachers‘ motivation. The continuous change in the teaching process alters the comprehension and principles of teaching substance. Every education organization is unique, having its own culture. Therefore, only the employees‘ ability to work creatively and innovatively influences the successful work of a school. The requirements of education reform motivate the teachers‘ and leaders‘ creativity and initiatives. However, only by solving the means of motivation correctly the teachers will be purposefully involved into the processes of school activity. The applied methods of analysis were analysis of scientific literature and documents, expert interview, analysis and interpretation of the research results. The article presents an overview of scientific literature. In addition, the results of the research may be applied in improving the school activity, motivating teachers for more effective work by considering the satisfaction of employees‘ needs. The research revealed the essential factors influencing teachers‘ motivation in schools.